How to remain balanced when developing a new kind of leadership - Sträng, Dan Roger (Vodenje v vzgoji in izobraževanju, 2014)
In this paper we will discuss the process of creating and implementing an efficient dialogue between educational leaders and researchers in a collaborative relationship. The dialogue was originally intended to help the leaders find new and effective ways to improve their leadership through reflective practice. A way of doing this was implementing a mentoring leadership which eventually ended up with a frustrated staff and questions of how educational leaders can attach to a new kind of leadership without losing their identity. Reflective practice may lead to learning and growth for the whole organization, but changing an organizational culture is complex and challenging for those involved.
Keywords: collaborative dialogue; dialog; education; leadership; medosebna komunikacija; mentorji; ravnatelji; reflective practice; vodenje